Предмет: Алгебра,
автор: МаринаСун
Ответы
Автор ответа:
0
Решение
x³/2√(x - 3) = (3x² + 8x)/√(x - 3)
x³/2√(x - 3) - (3x² + 8x)/√(x - 3) = 0
(x³ - 6x²- 16x)/2√(x - 3) = 0
x³ - 6x² - 16x = 0
x - 3 ≠ 0, x ≠ 3
x(x² - 6x - 16) = 0
x₁ = 0
x² - 6x - 16 = 0
x₂ = - 2
x₃ = 8
Ответ:x₁ = 0 ; x₂ = - 2 ; x₃ = 8
x³/2√(x - 3) = (3x² + 8x)/√(x - 3)
x³/2√(x - 3) - (3x² + 8x)/√(x - 3) = 0
(x³ - 6x²- 16x)/2√(x - 3) = 0
x³ - 6x² - 16x = 0
x - 3 ≠ 0, x ≠ 3
x(x² - 6x - 16) = 0
x₁ = 0
x² - 6x - 16 = 0
x₂ = - 2
x₃ = 8
Ответ:x₁ = 0 ; x₂ = - 2 ; x₃ = 8
Автор ответа:
0
Всего один ответ соответствует! Почему написали 3 ответа?
Похожие вопросы
Предмет: Английский язык,
автор: BossAlmat
Предмет: Английский язык,
автор: daniarzang
Предмет: Қазақ тiлi,
автор: aidostigerseil
Предмет: География,
автор: katekate2222
Предмет: География,
автор: mmm3682